The impact of biological age of red blood cell on in vitro endothelial activation markers - Alshalani, Abdulrahman; Beuger, Boukje M.; Tuip-de Boer, Anita M.; van Bruggen, Robin; Acker, Jason P.; Juffermans, Nicole P. (Frontiers in Physiology, 2023)
Introduction Blood donor characteristics influence red blood cell (RBC) transfusion outcomes. As donor sex affects the distribution of young to old RBCs in the circulation, we hypothesized that the amount of circulating young RBCs in the blood product are associated with immune suppression. Materials and Methods Blood samples were collected from healthy volunteers and density fractionated into young and old subpopulations. In an activated endothelial cell model, RBC adhesion to endothelium and secretion of endothelial activation markers were assessed. The impact of RBC biological age was also assessed in a T cell proliferation assay and in a whole blood stimulation assay. Results After Percoll fractionation, young RBCs contained more reticulocytes compared to old RBCs. Young RBCs associated with lower levels of E-selectin, ICAM-1, and vWF from activated endothelial cells compared to old RBCs. RBC subpopulations did not affect T cell proliferation or cytokine responses following whole blood stimulation. Conclusion Young RBCs contain more reticulocytes which are associated with lower levels of endothelial activation markers compared to old RBCs.